Does support for the legal right to an abortion differ across generations in the United States? - Carlisle Rainey; Robert A. Jackson (PLoS ONE, 2026)
The Supreme Court’s ruling in Dobbs v. Jackson Women’s Health Organization (2022) has reinvigorated interest in public opinion regarding abortion rights. Recent cross-sections of polling data reveal that young adults are strongly pro-choice and markedly more pro-choice than older adults—with accompanying commentary frequently reporting on the especially pro-choice attitudes of Generation Z and the prospect of the Court’s ruling becoming starkly counter-majoritarian. However, analysis of a single cross-section cannot distinguish differences between generations from differences between younger and older respondents . We examine the generational differences hypothesis carefully. Do data support the claim that attitudes toward the right to an abortion vary across generations? Analyzing five decades of General Social Survey (GSS) data, we use Bayesian hierarchical models to estimate the differences in respondents’ attitudes toward the legal right to an abortion in the United States across ages, survey years, and generations (specifically, the Silent Generation, Baby Boomers, Generation X, Millennials, and Generation Z). We find large differences in attitudes across ages and especially survey years, but only small differences across these generations. Beginning at about the age of 40, Americans have followed a consistent trajectory of increasingly conservative abortion attitudes. Finally, the large differences across survey years indicate that American public opinion toward abortion is malleable in the near term—with the data revealing contemporaneous, directional shifts in attitudes across society.